2016
DOI: 10.1111/bph.13510
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical studies of VS‐505: a non‐absorbable highly effective phosphate binder

Abstract: BACKGROUND AND PURPOSEPhosphate imbalance is often present in chronic kidney disease (CKD), and it contributes to a higher cardiovascular mortality rate. A phosphate binder is typically part of a treatment strategy for controlling phosphate imbalance. However, safety concerns and low compliance are two well-recognized disadvantages of on-market phosphate binders. This report describes the preclinical studies of VS-505, a non-absorbable, calcium-and aluminum-free, plant-derived polymer currently being evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…Another weakness of our studies is that we never performed chronic dosing or studied LY335896 in disease models. Others have reported beneficial effects of therapies that limit the phosphate absorption in rodent CKD models 42–46 . Using the clinically relevant doses employed in our studies, it is unlikely we would observe any benefits in a disease model, as we anticipate a little impact on the phosphate burden.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Another weakness of our studies is that we never performed chronic dosing or studied LY335896 in disease models. Others have reported beneficial effects of therapies that limit the phosphate absorption in rodent CKD models 42–46 . Using the clinically relevant doses employed in our studies, it is unlikely we would observe any benefits in a disease model, as we anticipate a little impact on the phosphate burden.…”
Section: Discussionmentioning
confidence: 85%
“…Others have reported beneficial effects of therapies that limit the phosphate absorption in rodent CKD models. [42][43][44][45][46] Using the clinically relevant doses employed in our studies, it is unlikely we would observe any benefits in a disease model, as we anticipate a little impact on the phosphate burden. Many studies that have shown benefit in preclinical renal disease models used very large doses of phosphate binders incorporated in the food (3%-5% of food or around 1.5 to 3.5 g/kg/day assuming standard rates of food consumption for rats and mice) that may produce effects on phosphate metabolism that cannot be achieved clinically or unanticipated side effects, for example, effects on food intake.…”
Section: Groupsmentioning
confidence: 98%
“…Setting a significance level at 5% (α = 0.05) and with a power of 80% (β = 0.80), the estimated number of animals was calculated at 16 per group. Taking into account a compensation of 30% for reported animal loss of 30–46% after 5/6 nephrectomy due to anatomical differences between animals and the complexity of the surgical procedure [ 30–32 ], the number of animals needed per group was 23. Therefore, in total, 46 animals were included in the study.…”
Section: Methodsmentioning
confidence: 99%
“…Several clinical and experimental studies have demonstrated that pathological synthesis of FGF-23 can be prevented with a phosphate binder in uremic conditions ( Ketteler et al, 2019 ; Neven et al, 2020 ; Mason et al, 2021 ) although other studies has no probed any changes in serum FGF-23 levels after the use of these treatments ( Chue et al, 2013 ; Ruggiero et al, 2019 ; Toussaint et al, 2020 ). When used in experimental animal models of CKD, phosphate binder reduced serum FGF-23 levels ( Ghorbanihaghjo et al, 2018 ) with a significant reduction in aortic calcification ( Finch et al, 2013 ; Wu-Wong et al, 2016 ). Moreover, serum phosphate levels can be controlled through the reduction of intestinal phosphate absorption by inhibiting the NaPi-2b cotransporter.…”
Section: Fibroblast Growth Factor-23-klotho Axis As Therapeutic Target In Renal Diseasementioning
confidence: 99%